Alteration in important quality traits and antioxidant activities in Brassica oleracea with Ogura cybrid cytoplasm. (17th April 2017) - Dey, Shyam S.; Bhatia, Reeta; Parkash, Chander; Sharma, Saharsh; Dabral, Manish; Mishra, Vibha; Bhardwaj, Ila; Sharma, Komal; Sharma, Vinod Kumar; Kumar, Raj
Abstract: In vegetable brassicas, cytoplasmic male sterility (CMS) system is the most preferred mechanism for hybrid seed production and Ogura cybrid cytoplasm is the only source used widely. Effects of the alien cybrid cytoplasm on important quality traits need to be understood for their effective use in breeding programme. In analysing 38 Ogura cybrid cytoplasm‐based cauliflower CMS lines, it was revealed that introgression of Ogura cytoplasm resulted in significant alteration in important quality traits. Cupric reducing antioxidant activity and ferric reducing ability of plasma values were increased up to 5–10 times in different genotypes. Among 38 analysed CMS lines, concentration of plant pigments such as anthocyanin, total chlorophylls and ascorbic acid was reduced in 21, 17 and 32 genotypes, respectively. However, the concentration of total carotenoids and β‐carotene was elevated in most of the CMS lines and total carotenoid was increased up to 20 times in the CMS line, Ogu13‐85‐2A. The results indicate the role of nuclear–cytoplasmic interaction and mitochondrial genome in determining concentration of different quality traits.